Nama Produk dalam Snack Jepang di Family Mart Nagoya: Kajian Lanskap linguistik - Tresnasari, Ningrum (Japanese Literature Study Program, Faculty of Letters, Dr. Soetomo University, 2025)
The product name is part of the brand identity that serves as a communication tool between the company and consumers. The product name must be able to create a strong perception of the superiority of a product and distinguish it from other similar products. This research aims to find out how the informational function and symbolic function contained in product names on Japanese snacks with the fami maru logo at Family Mart Nagoya. This research uses descriptive qualitative method by using the theoretical framework of Landscape Linguistics. The results show that the informational function contained in the product names of Japanese snacks is based on the basic ingredients, additional flavors, and food texture. Meanwhile, in the symbolic function, there are four types of Japanese writing used in product names in Japanese snacks with the fami maru logo at Family Mart Nagoya, including hiragana, katakana, romaji and kanji. Keywords: product names; Japanese snacks; Family Mart; Landscape Linguistics.